Functions and applications of RNA interference and small regulatory RNAs - Feng Xuezhu; Guang Shouhong (Acta Biochimica et Biophysica Sinica)
Small regulatory RNAs play a variety of crucial roles in eukaryotes, influencing gene regulation, developmental timing, antiviral defense, and genome integrity via a process termed RNA interference (RNAi). This process involves Argonaute/small RNA (AGO/sRNA) complexes that target transcripts via sequence complementarity and modulate gene expression and epigenetic modifications. RNAi is a highly conserved gene regulatory phenomenon that recognizes self- and non-self nucleic acids, thereby defending against invasive sequences. Since its discovery, RNAi has been widely applied in functional genomic studies and a range of practical applications. In this review, we focus on the current understanding of the biological roles of the RNAi pathway in transposon silencing, fertility, developmental regulation, immunity, stress responses, and acquired transgenerational inheritance. Additionally, we provide an overview of the applications of RNAi technology in biomedical research, agriculture, and therapeutics.